2016
DOI: 10.11138/ccmbm/2016.13.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab is really effective in the treatment of osteoporosis secondary to hypogonadism in prostate carcinoma patients? A prospective randomized multicenter international study

Abstract: SummaryIntroduction. Osteoporosis is a complication of androgen deprivation therapy (ADT) in men with prostate carcinoma. The best defense against osteoporosis in prostate cancer is to identify patients with a high risk for fracture during the first clinical visit, select an effective anti-osteoporosis agent, and advise the patient to change his lifestyle and diet to prevent further bone loss. New agents include denosumab, a human monoclonal antibody that inhibits the RANK ligand (RANKL). RANKL promotes the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 44 publications
0
23
0
1
Order By: Relevance
“…The peak bone mass achieved at maturity and the age of menopause are strong predictors of an increased risk for fracture. Bisphosphonates are the cornerstone for the treatment of osteoporosis [5] and are commonly prescribed for its treatment, both in women and men [6]. More recently, other drugs (i.e., teriparatide and denosumab) are often prescribed and showed a safety profile [7], even when prescribed for therapy of non-unions [8].…”
Section: Introductionmentioning
confidence: 99%
“…The peak bone mass achieved at maturity and the age of menopause are strong predictors of an increased risk for fracture. Bisphosphonates are the cornerstone for the treatment of osteoporosis [5] and are commonly prescribed for its treatment, both in women and men [6]. More recently, other drugs (i.e., teriparatide and denosumab) are often prescribed and showed a safety profile [7], even when prescribed for therapy of non-unions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 18 selected research papers, there were seven RCTs using denosumab in breast cancer and prostate cancer [9,[15][16][17][18][19][20]. Three of these RCTs evaluated the role of denosumab in breast cancer [16,17,18], while one evaluated the role of denosumab in prostate cancer [15]. There were two systematic reviews and meta-analyses that compared the role of denosumab with bisphosphonates in both prostate cancer and breast cancer [9,20].…”
Section: Resultsmentioning
confidence: 99%
“…Normally, estrogen has a key role in maintaining bone density in healthy postmenopausal women; estrogen acts on both osteoblasts and osteoclasts to decrease bone turnover by suppressing bone remodeling action [26]. Antihormonal therapy, whether it is ADT or AI therapy, ultimately decreases estrogen activity [15,27]. Figure 2 illustrates the mechanism of action of denosumab and bisphosphonates.…”
Section: Mechanism Of Action Of Denosumab and Bisphosphonatesmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the effects of denosumab and alendronate on BMD and fracture risk was performed in a randomized study of 234 prostate cancer patients on ADT. The authors found that denosumab was associated with a significant increase in BMD (measured at the lumbar spine) at 24 months compared to alendronate (5.6% vs 1.1%, p < 0.001) with a concomitant lower incidence of vertebral fractures, which was not statistically significant [92]. Denosumab is currently the only agent that has regulatory approval for the treatment of bone loss associated with hormone ablation in men with prostate cancer at increased risk of fractures.…”
Section: Denosumabmentioning
confidence: 97%